Efficiency of water application of irrigation systems based on microsprinkling in banana plantations (Scientia Agricola, 2013)
Further food production may be limited by the reduced availability of water resources. Since irrigated agriculture is the productive sector that presents a higher demand of water, this sector has been under intense pressure in order to ensure food production with improved efficiency of water use. This study aimed to use the Time Domain Reflectometry (TDR) technique to measure percolation losses and to determine water application efficiency of banana (Musa spp.) trees using microsprinkler irrigation systems. Three systems were studied: (i) one 32 L h-1 microsprinkler for four plants; (ii) one 60 L h-1 microsprinkler for four plants; and (iii) one 60 L h-1 microsprinkler for two plants. Systems that replace water to the soil with the lowest variation of infiltrated water depths at different distances from plant pseudostem were the most efficient. The water application efficiency of microsprinkler irrigation systems using the (i), (ii), and (iii) microsprinkler systems were 85%, 80 % and 90 % respectively.